A comparative analysis of auxiliary enforcement bodies for security, safety and health officer roles in Malaysia a narrative review - Ismail, Hassan; Zainal Abidin, Emilia; Rasdi, Irniza; K.C. Mani@Subramaniam, Kulanthayan; Phaik, Kin Cheah (Universiti Putra Malaysia, 2023)
Overlapping of job function between safety and health officers, auxiliary enforcement bodies (AEB), and private security guards emphasise a need to identify possible merging of roles in a new integrated job model to manage security, safety, and health more efficiently. The purpose of paper is to compare four main enforcement agencies in Malaysia namely the Auxiliary Police, Malaysian Volunteer Corps Department, private Security Guards and Safety and Health Officers. Employing the narrative review technique, information was collected from official reports, legal documents and publications to find commonalities. Five main themes generated from the analysis are: roles, legislation, history, manpower and lastly renumeration and training. Practical implications of an integrated role in cross-national contexts were discussed. Legal implications need to be explored on existing responsibilities and the additional proposed roles for when their functions are integrated and the impact on supervision needs and budget allocation. Social implications are important to consolidate job models to reduce occupational accidents.